Analisis Balancing Roda Metode Sudut Fasa pada Putaran Kritis - Rudi Hartono (Program Studi Teknik Mesin Universitas Khairun, 2018)
Vibration on the vehicle causes problems on stability, comfort and reduced lifetime of part. Balancing is solution to reduce the vibration, This research discuss at methode phase angle balance, this metode can determine location the mass unbalance. The vibration that occur read by tranducer and accelerometer receive the signal and sent to computer. The Program Pico can read the characteristic of vibration and the marked of , photoelectric read. The distance of the mass unbalnce identified by location of the mark and amplitude. The rpm of whell is 400 -600, the location of the mass unbalance and the mass balance is 180 o. The balancing process and the mass balance. The peak of amplitudo vibration on 505 rpm and the location of the mass unbalance 9,390, and the balance performance is 0,74. Phase angle methode has a precision that can read the location appropriate unbalance mass and have good balance performance